Wastewater Channel And Escherichia Coli In Wells, Desa Durin Simbelang Kecamatan Pancur Batu - Seri Asnawati Munthe; Lia Rosa Veronika Sinaga; Jasmen Manurung (Akupun Tour Publisher, 2022)
Background : Water is the most important substance in life. About three quarters of our body consists of water and no person can survive more than 4-5 days without drinking water. Water is used for cooking, washing, bathing, and cleaning waste. around the house. Water is also used for industrial purposes, agriculture, fire fighting, recreation, transportation, and others. Water can spread and transmit disease to humans. These conditions can certainly cause disease outbreaks. can be separated from human life. Clean water contaminated with Escherichia coli bacteria is one of the causes of diarrheal disease. Purpose: The purpose study is to know relationship of wastewater channel and Escherichia Coli Levels In Wells, Durin Simbelang Village, Pancur Batu District. Method: This study used an analytical survey method with a cross sectional design using simple random sampling. The number of samples is 30 dug wells and statistical analysis using Chi square test. Results: There is 53.3% of wastewater channel with high contamination risk and 56.7% of dug wells contaminated with Escherichia coli bacteria. From the statistical results, it was found that there was a relationship between sanitation in wastewater channel(p value 0.269) with E.Coli content. Conslusion: the advice given by the researcher is that if it is used as drinking water, it should be boiled until it boils, giving disinfectant to dug wells to make it safer to use for hygiene and sanitation needs.